Biochemical and Physiological Predictors of Severe Dehydration in Children Under Five - Sobia Ali, Jalil Khan, Dr Rahat Jan Wazir, Amber Zaidi, Roshaan Bashir, Sidra Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute diarrhea and vomiting in children under five years of age is one of the most serious complications and that is dehydration. If left untreated and unchecked, severe dehydration can quickly lead to electrolyte disorders, metabolic acidosis, renal hypoperfusion, shock and death. Biochemical abnormalities may also give some clues as to the severity and risk of complications, but the clinical signs will still be the first line of diagnosis. Objective: To determine the biochemical and physiological predictors of severe dehydration in children under five years of age. Methods: This descriptive cross-sectional study was conducted at from January 2022 to January 2023. The children were sampled consecutively, and a total of 72 children below age of 5 years with dehydration secondary to acute diarrhea and/or vomiting were included. Demographic, clinical data and physiological parameters such as heart rate, respiratory rate, capillary refill time, blood pressure, peripheral pulse, extremity temperature, skin turgor, sunken eyes, level of consciousness, drinking ability and urine output were documented. Blood samples were drawn to measure the serum sodium, potassium, chloride, bicarbonate, blood urea, serum creatinine and random blood glucose. Children were divided into two groups, non-severe and severe dehydration. The SPSS version 25 software was used for data analysis. The P value was used to determine statistical significance with a cutoff of less than 0.05. Results: Among 72 children, 26 (36.1%) had severe dehydration, while 46 (63.9%) had non-severe dehydration. Severe dehydration was more frequent among infants below 12 months and children with underweight or wasted nutritional status. Physiological predictors significantly associated with severe dehydration included tachycardia, tachypnea, capillary refill time greater than two seconds, low blood pressure, cold extremities, weak peripheral pulse, sunken eyes, very slow skin pinch, lethargy or unconsciousness, and poor urine output. Biochemical abnormalities including low serum bicarbonate, raised blood urea, raised serum creatinine, hyponatremia, hypernatremia, and hypokalemia were significantly more common in children with severe dehydration. On multivariate analysis, capillary refill time greater than two seconds, very slow skin pinch, poor urine output, low serum bicarbonate, and raised blood urea were independent predictors of severe dehydration. Conclusion: Severe dehydration was common among children under five presenting with acute diarrhea and vomiting. Delayed capillary refill time, very slow skin pinch, poor urine output, low bicarbonate, and raised blood urea were important predictors of severe dehydration. Early recognition of these physiological and biochemical indicators can help guide timely management and reduce dehydration-related complications. Keywords: Severe dehydration, children under five, diarrhea, biochemical predictors, physiological predictors, electrolytes, bicarbonate.